Spaces of consent and the making of fracking subjects in North Dakota: A view from two corporate community forums. Issue 3 (July 2016) - Loder, Thomas
Abstract: Although hydraulic fracturing (fracking) has become a key area of analysis in extractive studies, North Dakota's Bakken Formation has been largely ignored. In addition, while scholars have begun to link subject formation with environmental behavior, explicit reference to existing theories of environmentality have been noticeably absent. This essay seeks to both introduce the Bakken to ethnographic studies of fracking as well as explicitly provide a model for using environmentality alongside existing political economic approaches. Such engagements help not only to better connect fracking subjectivities to larger societal processes, but also allows for the drawing of connections with bodies of literature on subjectivity and institutional analysis.